Hybridization between Malaysian mahseer [Tor tambroides, (Bleeker, 1854) ♂] and silver barb [Barbonymus gonionotus, (Bleeker, 1850) ♀] for new strain development and their susceptibility to low salinity tolerance - Mohamed Azahar, Siti Nur Ain (2019)
New hybrid was introduced in this study using induce breeding technique. The desire of this study to investigated the embryonic development and the morphometric differences of hybrid while observed the physical and their tolerance limits in stressed condition due to water salinity exposure. Silver barb (Barbonymus gonionotus) broodstocks were induced by Ovatide hormone and their eggs were fertilized with non-treated milt of Malaysian mahseer (Tor tambroides). No hormonal injection was given to male broodstock because of sperm availability. The embryonic development were observed by stages at every 15, 30, 45 min and 1 hours interval till completion of cleavage until hatching. Morphometric analysis was done to detect external shape differences between hybrid and their maternal parent using truss network measurement. For salinity experiment, different tolerance of salinity at 0, 3, 6, and 9 ppt were exposed for 8 weeks. All treatments were triplicated, labelled and arranged in a randomized design. Fry were fed until satiation twice a day and 30% water changes once every two day. New strains of hybrid Malaysian mahseer was successful breed and the first cleavage showed at 0.06 h after fertilization and hatched at 13.00 h after hatching with fertilization rates (74.16 ± 0.7%) and hatching rates (4.5-7.4%). The mean total length of newly hatched larvae was 4.03±0.28 mm. Morphological differences between hybrid Malaysian mahseer and Silver barb (Barbonymus gonionotus) were analysed. Out of the total of 21 transformed truss measurements, 12 showed highly significant (p < 0.01) differences among hybrid Malaysian mahseer and Barbonymus gonionotus. Furthermore, the hybrid showed the highest growth rate and survival rate (84±7.78%) of fry was obtained in water of salinity of 3 ppt. The lowest growth performance and survival rate (67±13.45%) occurred in 0 ppt. The highest body weight and lengths of larvae were observed in water of salinity 9ppt. However, significant histological alterations were observed at 9 ppt which caused major histological anomalies such as structural alterations in the portal vein, vacuolation, necrotic hepatocytes, aggregation of blood cells and melanomacrophages. Results have shown that high salinity in the aquatic condition affects the health condition of the hybrid fry. The optimal condition for culture of the hybrid was obtained at 3ppt. The valuable knowledge and information emerged from this designated studies will ultimately be useful towards massive hybrid production and better understanding the optimal condition for cultural this hybrid.